Preplanned City: BGI in Songdo - Afful, Gingles Nii; Lee, Keon-Ho; Worden, Alex (Street Art & Urban Creativity, 2025)
Over the past few decades, Blue-green infrastructure (BGI) has emerged as one of the cornerstones of sustainable urban development, balancing ecological restoration, climate resilience, and human well-being. Cities across the globe have different policy frameworks, design priorities, and governance structures that shape the implementation of BGI systems. In South Korea, in particular, Songdo’s design highlights how a top-down, master-planned eco-city integrates BGI with smart city technologies and climate adaptation measures. In New York City, decentralized implementation and public–private partnerships have been vital to scaling up BGI. In Singapore, the nation-state illustrates a nationally coordinated approach, positioning BGI as both ecological infrastructure and a critical climate adaptation strategy. Vienna offers a contrasting European model, where BGI is closely related to long-term planning traditions. Together, these diverse governance models highlight how BGI can be tailored to local environmental, social, and political contexts while contributing to global climate resilience and human enjoyment.